Multi-element metal oxide integrated electrode and preparation method thereof

The carbon cloth and PEI solution were pretreated by concentrated nitric acid hydrothermal method, and combined with the electrojoule heat method, an efficient and uniformly dispersed composite oxygen-elimination catalytic electrode was prepared, which solved the problems of complex preparation process, large energy consumption and uneven material in the prior art, achieved high activity, low cost and good stability, and met the requirements of industrial applications.

CN119506967APending Publication Date: 2025-02-25XIAN TECH UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411220325.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-02
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing OER electrocatalyst preparation process is complex and has large energy consumption. The material grows unevenly on the carbon support carrier and has poor stability at high current density, which cannot meet the actual working conditions requirements of the PEMWE electrolytic cell.

Method used

The carbon cloth was pretreated by concentrated nitric acid hydrothermal method to enhance its hydrophilicity and active sites; the carbon cloth was treated with PEI solution to uniformly disperse metal ions; and the RuO2 and Co3O4 composite oxygen-elimination catalytic electrode was rapidly synthesized by one-step reaction of the electrojoule heat method.

Benefits of technology

It realizes an efficient and uniform dispersed multi-metal oxide integrated electrode, which has high activity, low cost and good stability, and can work stably for a long time under high current density, meeting the requirements of industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119506967A_ABST
    Figure CN119506967A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of application of electro-catalytic materials, and particularly relates to a multi-element metal oxide integrated electrode and a preparation method thereof. The electrode is prepared by a one-step Joule thermal method and comprises the following steps: step 1, pretreating the surface of a carbon-based substrate by using a polyethyleneimine aqueous solution and drying; 2, dissolving the transition metal salt and precious metal salt hydrate in ethanol to obtain a precursor solution; 3, uniformly dripping the precursor solution on the surface of a carbon-based substrate for dipping, and carrying out vacuum drying; and 4, rapidly heating the carbon-based substrate by using electric Joule thermal equipment to prepare the catalytic electrode. The method is simple, the multi-metal oxide integrated electrode which is high in activity, low in cost and uniform in dispersion is rapidly synthesized in a short time, and the catalyst can effectively support efficient oxygen evolution reaction under acidic and alkaline conditions; the preparation method is suitable for large-scale industrial production of the electrolyzed water OER catalytic electrode, and can be widely applied to the application fields of electrolytic cells and fuel cells.
Need to check novelty before this filing date? Find Prior Art

Description

Technical field:

[0001] The invention belongs to the field of application of electrocatalytic materials, and in particular relates to a method for preparing a multi-metal oxide integrated electrode. Background technology:

[0002] Hydrogen energy, which is widely used in the field of energy storage, has the advantages of wide sources, high combustion calorific value, clean and pollution-free, and good safety. The use of proton exchange membrane fuel cell technology, which is currently in the commercial stage, is very mature, but the source and cost of hydrogen energy restrict the application and progress of fuel cells. Renewable water electrolysis to produce hydrogen is an important way to source hydrogen. The hydrogen produced is of high purity and the production method is clean and pollution-free. Water electrolysis to produce hydrogen includes two-terminal reactions, one end is the HER hydrogen evolution reaction, and the other end is the OER oxygen evolution reaction. The OER reaction involves the transfer of four electrons, which complicates the entire reaction mechanism. Compared with the hydrogen evolution reaction, the kinetics are slow and the overpotential is higher. The OER process includes four steps. First, water molecules are oxidized on the surface of the catalyst M to form MOH, and transfer an electron and a proton. Secondly, the generated MOH is further oxidized to a MO intermediate. Third, another water molecule is oxidized on the MO intermediate to form a superoxide intermediate MOOH. Finally, the MOOH intermediate is oxidized to oxygen molecules and desorbed on the surface. Surface self-reconstruction usually occurs during the OER process, which tends to increase the activity of the electrode. However, the OER process produces oxygen and oxygen vacancies that dissolve metal ions in the solution, reducing the stability of the catalyst. Currently, commercial OER electrocatalysts are mainly RuO2 and IrO2, but their high cost and poor activity and stability limit their large-scale use in industry. Inexpensive non-precious transition metal oxides such as Co, Ni, Cu, Mn, and Zn theoretically have certain OER activity. Therefore, the development of efficient and inexpensive oxygen evolution (OER) electrocatalysts is currently of vital importance.

[0003] Spinel transition metal Co oxide has high OER activity and is an ideal material to replace RuO2 oxygen evolution electrocatalyst. Many theoretical and practical application results have been reported on the application of Co3O4 in OER, and it is found that its activity has greater room for improvement. The oxygen evolution catalyst formed by the composite of RuO2 and Co3O4 can effectively improve the activity and stability, and can reduce the amount of precious metals. In addition, in order to improve the conductivity of the material, carbon materials can be introduced. Carbon materials have porous properties and large specific surface areas, which can effectively disperse the active components in the catalyst, avoid the reduction of activity caused by agglomeration, and expose more active sites, as well as accelerate the charge transfer and mass transfer of bubbles during the reaction.

[0004] The document with application number "202210587000.0" discloses "a cobalt niobium oxide OER electrocatalyst and its preparation method and application". The invention mixes cobalt salt, niobium salt, ammonium fluoride and urea in water to obtain a precursor liquid; then the conductive carbon is arranged in the precursor solution for hydrothermal reaction, and then the solid-liquid separation, washing and drying are performed to obtain a carbon cloth-loaded Co(OH)2 / Nb(OH)5 precursor; finally, the precursor is sintered in air to obtain a Co3O4 / Nb2O5@CC electrocatalyst. The problems with this scheme are: 1. The catalyst is prepared in two steps, which is a complicated process and consumes a lot of energy; 2. The hydrothermal growth method cannot ensure that the material grows evenly on the carbon support carrier; 3. The catalyst is 10mAcm in acid and alkaline solutions. -2 The overpotentials at current densities of 390 mV and 289 mV are respectively, and they can only work at low current densities. -2 It can work stably for 48 hours at a current density of , which cannot meet the actual operating requirements of PEMWE electrolyzers at the ampere level, corrosion resistance and long life. Summary of the invention:

[0005] The present invention provides a multi-metal oxide integrated electrode and a preparation method thereof, so as to overcome the problems existing in the prior art of complex process, high energy consumption, failure to ensure uniform growth of materials on a carbon support carrier, and failure to meet the actual operating requirements of the PEMWE electrolyzer for ampere-level current density, corrosion resistance and long life.

[0006] In order to achieve the purpose of the present invention, the technical solution provided by the present invention is: a method for preparing a multi-metal oxide integrated electrode, comprising the following steps:

[0007] Step 1: soaking the pretreated carbon-based substrate in a polyethyleneimine aqueous solution and drying it for later use; dissolving a transition metal salt and a ruthenium salt hydrate in ethanol to prepare a precursor solution, wherein the transition metal is Co, Cu, Mn, Ni or Zn;

[0008] Step 2: Place the carbon-based substrate in a culture dish, take a certain amount of precursor solution and drip it on the surface of the carbon-based substrate to completely cover it, soak it for 30 to 40 minutes, and then place it in a vacuum oven to dry for 6 to 8 hours;

[0009] Step 3: subjecting the carbon-based substrate to electric Joule heat treatment at 400-800°C.

[0010] Furthermore, the above-mentioned carbon-based substrate is selected from one or more carbon-based substrates such as carbon cloth, carbon paper, carbon felt, etc.; the pretreatment of the step one is: immersing the carbon-based substrate material in a hydrothermal reactor filled with 65% concentrated nitric acid, sealing it at 80-100°C, keeping it warm for 12-15 hours, taking out the carbon cloth after cooling, ultrasonically treating it with anhydrous ethanol and deionized water, and then vacuum drying it to obtain a pretreated carbon-based substrate.

[0011] Furthermore, the above transition metal salt is selected from one or more of chlorides, nitrates and acetates.

[0012] Furthermore, the above-mentioned ruthenium salt hydrate is selected from one or more of ruthenium chloride hydrate and ruthenium acetylacetonate.

[0013] Furthermore, the molar ratio of the transition metal to ruthenium is 1:1, 2:1 or 3:1.

[0014] Furthermore, the loading amount of the noble metal ruthenium is 0.3-0.7 mg / cm 2 .

[0015] Furthermore, in the above step three, the Joule thermal voltage is 25 to 45 V, the current is 35 to 55 A, the number of pulses is 3 times, and the heating time for each time is 0.1 to 0.5 s.

[0016] Furthermore, the Joule heat atmosphere is one or more of air, vacuum, and nitrogen atmosphere.

[0017] Furthermore, the above preparation method produces an integrated electrode of multi-metal oxides.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] 1. The present invention uses concentrated nitric acid to pretreat carbon cloth through a hydrothermal method, so that defects are generated on the surface of the carbon cloth, which enhances the hydrophilicity of the carbon cloth, can evenly disperse the growing nanoparticles, expose more active sites, and also enhance the mass transfer capacity of the catalyst, accelerate the detachment of bubbles, so that the catalyst can have efficient catalytic activity even under high current.

[0020] 2. The present invention uses PEI solution to treat the carbon cloth before impregnation. Since PEI, as a polymer with high C and N content, presents a positive charge in the solution, it can accumulate metal ions, thereby making the metal ions evenly and quickly dispersed on the surface of the carbon cloth.

[0021] 3. The present invention uses the electric Joule heating method to quickly synthesize the RuO2 and Co3O4 composite oxygen evolution catalytic electrode on carbon cloth in a short time. Compared with the traditional technology, the reaction time and cooling rate are fast, the energy consumption is low, and the material is evenly dispersed. The method of the present invention is simple and can quickly synthesize a highly active, low-cost, and evenly dispersed multi-metal oxide integrated electrode in a short time.

[0022] 4. The loading amount of precious metal in the catalyst of the present invention is controlled at 1 mg / cm 2 The noble metal utilization rate is high within 100%, and the catalyst still has efficient OER activity at low noble metal loading. The electrode exhibits excellent and stable OER activity in acidic and alkaline media, reaching 10 mA / cm in acidic media. 2 The overpotential required for catalytic current density ranges from 207 to 729 mV, reaching 10 mA / cm in alkaline medium. 2 The overpotential range required for the catalytic current density is 190 to 322 mV. It operates stably for 110 hours at a constant voltage of 1.54 V (vs. RHE). Therefore, the preparation method of the present invention is suitable for large-scale industrial production of water electrolysis OER catalytic electrodes, which can meet the actual working conditions requirements of PEMWE electrolyzers with ampere-level current density, corrosion resistance and long life, and is widely used in electrolyzers and fuel cell applications. Description of the drawings:

[0023] Figure 1 It is the XRD diagram of Example 1, Example 2, and Example 3;

[0024] Figure 2 It is the SEM picture of Example 1, Example 2, and Example 3;

[0025] Figure 3 LSV diagrams of Example 1, Example 2, and Example 3 in 0.5 mH2SO4;

[0026] Figure 4 It is the XRD diagram of Example 1, Example 4 and Example 5;

[0027] Figure 5 The SEM images of Example 1, Example 4 and Example 5 are shown;

[0028] Figure 6 LSV diagrams of Example 1, Example 4 and Example 5 in 0.5 mH2SO4;

[0029] Figure 7 The XRD patterns of Example 1, Example 6 and Example 7 are shown in FIG.

[0030] Figure 8 The SEM images of Example 1, Example 6 and Example 7 are shown;

[0031] Fig. 9 LSV diagrams of Example 1, Example 6 and Example 7 in 0.5 mH2SO4;

[0032] Fig.10 LSV diagrams of Example 1, Example 8 and Example 9 in 0.5 mH2SO4;

[0033] Fig.11 1 is the XRD diagram of Example 1, Example 8 and Example 9;

[0034] Fig.12 LSV diagrams of Example 10, Example 11, Example 12 and Example 13 in 0.5 mH2SO4;

[0035] Fig.13 LSV diagrams of Example 1, Comparative Example 1 and Comparative Example 2 in 0.5 mH2SO4 and 1 mKOH;

[0036] Fig.14 The XRD diagrams of Example 1, Comparative Example 1 and Comparative Example 2 are shown in FIG.

[0037] Fig.15 The SEM images of Example 1, Comparative Example 1, Comparative Example 2 and the EDS image of Example 1 are shown;

[0038] Fig.16 This is a constant voltage chronoamperometry CA test diagram of Example 1 at a constant potential of 1.54 V (Vvs.RHE);

[0039] Fig.17 SEM images before (a) and after (b) the OER stability test of Example 1. Specific implementation method:

[0040] The present invention will be described in detail below with reference to the accompanying drawings and embodiments.

[0041] Embodiment 1, a method for preparing a multi-element metal oxide integrated electrode, comprising the following steps:

[0042] The first step is to immerse a 1*2.5cm rectangular carbon cloth in a hydrothermal reactor filled with 65% concentrated nitric acid, seal it and keep it at 90°C for 12h, take out the carbon cloth after cooling, ultrasonically treat it with anhydrous ethanol and deionized water, and then vacuum dry it to obtain a pretreated carbon cloth. The pretreated carbon cloth is immersed in a polyethyleneimine solution (4mg / ml) and treated at 60°C for 1h, then the carbon cloth is taken out and rinsed with deionized water and dried.

[0043] Step 2: Weigh 13 mg of cobalt chloride hexahydrate and 12.5 mg of ruthenium chloride hydrate, mix them in 500 μL of ethanol, take 100 μL of the precursor solution and drop it evenly on the surface of the carbon cloth, immerse for 30 minutes, and vacuum dry for 6 hours.

[0044] The third step is to subject the dried carbon cloth to electric Joule heating in air, where the voltage is 35 V, the current is 45 A, and pulse heating is performed three times at 600 ° C, with each pulse heating time being 0.1 s. After the Joule heating is completed, the RuO2-Co3O4 / CC composite oxide OER catalytic electrode can be obtained.

[0045] Example 2, a method for preparing a multi-metal oxide integrated electrode, is the same as Example 1, except for the third step: in air, the dry carbon cloth is subjected to electric Joule heat treatment, wherein the voltage is 25V, the current is 35A, and pulse heating is performed 3 times at 400°C, and each pulse heating time is 0.1s.

[0046] Example 3, a method for preparing a multi-metal oxide integrated electrode, is the same as Example 1, except for the third step: in air, the dry carbon cloth is subjected to electric Joule heat treatment, wherein the voltage is 45V, the current is 55A, and pulse heating is performed 3 times at 800°C, and each pulse heating time is 0.1s.

[0047] See also Figure 1 The XRD comparison diagrams of the above three embodiments show that the crystallinity of the catalyst is better when sintered at 600°C.

[0048] See also Figure 2 The SEM comparison images of the above three embodiments show that the higher the temperature, the more obvious the particle agglomeration, resulting in the covering of active sites, thus reducing the catalytic activity.

[0049] See also Figure 3 The LSV diagrams of the above three embodiments show that the OER oxygen evolution overpotential of the catalyst is the lowest when sintered at 600°C, and η10 is only 214mV.

[0050] Example 4, a method for preparing a multi-metal oxide integrated electrode, is the same as Example 1, except for the second step: weigh 26 mg of cobalt chloride hexahydrate and 12.5 mg of ruthenium chloride hydrate, mix them in 500 μL of ethanol, take 100 μL of the precursor solution and evenly drop it on the surface of the carbon cloth, immerse for 30 minutes, and vacuum dry for 6 hours.

[0051] Example 5, a method for preparing a multi-metal oxide integrated electrode, is the same as Example 1, except for the second step: weigh 6 mg of cobalt chloride hexahydrate and 12.5 mg of ruthenium chloride hydrate, mix them in 500 μL of ethanol, take 100 μL of the precursor solution and evenly drop it on the surface of the carbon cloth, immerse for 30 minutes, and vacuum dry for 6 hours.

[0052] See also Figure 4 The XRD comparison diagrams of the above two embodiments and embodiment 1 show that the XRD diagrams show obvious differences after changing the ratio of Ru and Co, but the physical phase and crystal structure do not change, and the peak position does not change.

[0053] See also Figure 5 The SEM comparison images of the above two embodiments and embodiment 1 show that after increasing the Co content, the particles are obviously agglomerated, resulting in a decrease in activity.

[0054] See also Figure 6 The LSV comparison diagram of the above two examples and Example 1 shows that when Ru:Co is 3:1, the catalyst is at 10mAcm -2 The overpotential under current density is slightly higher than that at 2:1, but the performance under high current density is significantly lower than that of Example 1.

[0055] Example 6, a method for preparing a multi-metal oxide integrated electrode, is the same as Example 1, except for the third step: in air, the dry carbon cloth is subjected to electric Joule heat treatment, wherein the voltage is 30V, the current is 40A, and pulse heating is performed 3 times at 600°C, and each pulse heating time is 0.3s.

[0056] Example 7, a method for preparing a multi-metal oxide integrated electrode, is the same as Example 1, except for the third step: in air, the dry carbon cloth is subjected to electric Joule heat treatment, wherein the voltage is 25V, the current is 35A, and pulse heating is performed 3 times at 600°C, and each pulse heating time is 0.5s.

[0057] See also Figure 7 The XRD comparison diagrams of the above two embodiments and embodiment 1 show that the peak position and peak intensity in the XRD diagram do not change after changing the Joule heating time.

[0058] See also Figure 8 The SEM comparison diagrams of the above two embodiments and embodiment 1 show that the longer the heating time, the larger the particle size and the more obvious the agglomeration, thus reducing the OER activity.

[0059] See also Fig. 9The LSV comparison diagram of the above two embodiments and embodiment 1 shows that the catalyst has better OER performance at a heating time of 0.1 s. This is because the particle size of the catalyst is smaller and the particle distribution is more uniform.

[0060] Example 8, a method for preparing a multi-metal oxide integrated electrode, is the same as Example 1, except for the second step: weigh 8 mg of cobalt chloride hexahydrate and 7.5 mg of ruthenium chloride hydrate, mix them in 500 μL of ethanol, take 100 μL of the precursor solution and evenly drop it on the surface of the carbon cloth, immerse for 30 minutes, and vacuum dry for 6 hours.

[0061] Example 9, a method for preparing a multi-metal oxide integrated electrode, is the same as Example 1, except for the second step: weigh 18 mg of cobalt chloride hexahydrate and 17.5 mg of ruthenium chloride hydrate, mix them in 500 μL of ethanol, take 100 μL of the precursor solution and evenly drop it on the surface of the carbon cloth, immerse for 30 minutes, and vacuum dry for 6 hours.

[0062] See also Fig.10 The LSV comparison diagram of the above two examples and Example 1 shows that when the Ru loading is 0.5 mg / cm 2 The catalyst has better OER performance.

[0063] See also Fig.11 The XRD comparison diagrams of the above two embodiments and embodiment 1 show that the physical phase and crystal structure of the catalyst do not change after changing the Ru loading amount.

[0064] Example 10, a method for preparing a multi-metal oxide integrated electrode, is the same as Example 1, except for the second step: weigh 13 mg of nickel chloride hexahydrate and 12.5 mg of ruthenium chloride hydrate, mix them in 500 μL of ethanol, take 100 μL of the precursor solution and evenly drop it on the surface of the carbon cloth, immerse for 30 minutes, and vacuum dry for 6 hours.

[0065] Example 11, a method for preparing a multi-metal oxide integrated electrode, is the same as Example 1, except for the second step: weigh 11 mg of manganese chloride tetrahydrate and 12.5 mg of ruthenium chloride hydrate, mix them in 500 μL of ethanol, take 100 μL of the precursor solution and evenly drop it on the surface of the carbon cloth, immerse for 30 minutes, and vacuum dry for 6 hours.

[0066] Example 12, a method for preparing a multi-metal oxide integrated electrode, is the same as Example 1, except for the second step: weigh 7 mg of anhydrous cupric chloride and 12.5 mg of ruthenium chloride hydrate, mix them in 500 μL of ethanol, take 100 μL of the precursor solution and evenly drop it on the surface of the carbon cloth, immerse for 30 minutes, and vacuum dry for 6 hours.

[0067] Example 13, a method for preparing a multi-metal oxide integrated electrode, is the same as Example 1, except for the second step: weigh 7 mg of anhydrous zinc chloride and 12.5 mg of ruthenium chloride hydrate, mix them in 500 μL of ethanol, take 100 μL of the precursor solution and evenly drop it on the surface of the carbon cloth, immerse for 30 minutes, and vacuum dry for 6 hours.

[0068] See also Fig.12 Ni, Mn, Cu, Zn oxides and RuO2 can also show excellent OER activity when combined. -2 The overpotentials at current densities of 212, 208, 212, and 205 mV are respectively. -2 The overpotentials at current densities are 512, 559, 505, and 519 mV respectively.

[0069] Comparative Example 1, a method for preparing an electrode, is the same as Example 1, except for the second step: only 12.5 mg of ruthenium chloride hydrate is weighed, mixed in 500 μL of ethanol, 100 μL of the precursor solution is evenly dropped on the surface of the carbon cloth, immersed for 30 minutes, and vacuum dried for 6 hours.

[0070] Comparative Example 2, a method for preparing an electrode, is the same as Example 1, except that in the second step: only 13 mg of cobalt chloride hexahydrate is weighed, mixed in 500 μL of ethanol, 100 μL of the precursor solution is evenly dropped on the surface of the carbon cloth, immersed for 30 min, and vacuum dried for 6 h.

[0071] See also Fig.13 The LSV comparison diagram of Example 1, Comparative Example 1 and Comparative Example 2 shows that Example 1 has excellent OER activity in both acidic and alkaline conditions, while the OER activity of the single RuO2 and Co3O4 catalysts loaded on carbon cloth is poor, indicating that Co promotes the activity of RuO2.

[0072] See also Fig.14 The XRD pattern of RuO2-Co3O4 / CC shows the (101) crystal plane of RuO2 and the (311) and (422) crystal planes of Co3O4. The XRD pattern of RuO2 / CC only shows the crystal plane of C, and no other peaks exist, indicating that RuO2 exists in an amorphous form. The XRD pattern of Co3O4 / CC shows the characteristic peaks of the crystal plane of Co3O4, which is consistent with the corresponding peaks on the PDF card.

[0073] See also Fig.15 ,The SEM image of Example 1 shows that after the Co oxide composite, the particles are more evenly distributed on the surface and no other ,agglomerated particles are generated.

[0074] See also Fig.16The catalyst of Example 1 can stably operate at a voltage of 1.54 V (vs. RHE) for 110 h.

[0075] See also Fig.17 After 110 h of OER test, the morphology of the catalyst of Example 1 did not change, so the catalyst has excellent stability.

[0076] In summary, Example 1 of the present invention is the best embodiment. The obtained self-supporting integrated electrode has a high specific surface area and a porous structure, increases the active sites, and the composite oxides of Co and Ru are evenly dispersed on the surface of the carbon cloth. The promotion effect of Co effectively increases the OER activity of RuO2, and can achieve stable oxygen evolution in ampere-level acidic water electrolysis, and the amount of precious metals used is low, which can be commercially applied.

[0077] The above are only specific embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a multi-metal oxide integrated electrode, characterized in that: The following steps are involved: Step 1: soaking the pretreated carbon-based substrate in a polyethyleneimine aqueous solution and drying it for later use; dissolving a transition metal salt and a ruthenium salt hydrate in ethanol to prepare a precursor solution, wherein the transition metal is Co, Cu, Mn, Ni or Zn; Step 2: Place the carbon-based substrate in a culture dish, take a certain amount of precursor solution and drip it on the surface of the carbon-based substrate to completely cover it, soak it for 30 to 40 minutes, and then place it in a vacuum oven to dry for 6 to 8 hours; Step 3: subjecting the carbon-based substrate to electric Joule heat treatment at 400-800°C.

2. The method for preparing a multi-metal oxide integrated electrode according to claim 1, characterized in that: The carbon-based substrate is selected from one or more carbon-based substrates such as carbon cloth, carbon paper, and carbon felt; The pretreatment of step 1 is as follows: immersing the carbon-based substrate material in a hydrothermal reactor filled with 65% concentrated nitric acid, sealing it at 80-100° C., keeping it warm for 12-15 hours, taking out the carbon cloth after cooling down, ultrasonically treating it with anhydrous ethanol and deionized water, and then vacuum drying it to obtain a pretreated carbon-based substrate.

3. The method for preparing a multi-element metal oxide integrated electrode according to claim 1, characterized in that: The transition metal salt is selected from one or more of chlorides, nitrates and acetates.

4. The method for preparing a multi-metal oxide integrated electrode according to claim 1, characterized in that: The ruthenium salt hydrate is selected from one or more of ruthenium chloride hydrate and ruthenium acetylacetonate.

5. The method for preparing a multi-element metal oxide integrated electrode according to claim 1, characterized in that: The molar ratio of the transition metal to ruthenium is 1:1, 2:1 or 3:

1.

6. The method for preparing a multi-element metal oxide integrated electrode according to claim 1, characterized in that: The loading amount of the noble metal ruthenium is 0.3-0.7 mg / cm 2 .

7. The method for preparing a multi-element metal oxide integrated electrode according to claim 1, characterized in that: In the step three, the Joule thermal voltage is 25 to 45 V, the current is 35 to 55 A, the number of pulses is 3, and the heating time for each time is 0.1 to 0.5 s.

8. The method for preparing a multi-element metal oxide integrated electrode according to claim 1, characterized in that: The Joule heat atmosphere is one or more of air, vacuum, and nitrogen atmosphere.

9. The multi-metal oxide integrated electrode obtained by the preparation method according to claim 1.

Citation Information

Patent Citations

  • Cobalt niobium oxide OER electrocatalyst and preparation method and application thereof

    CN115125571A